PERANCANGAN APLIKASI KUMPULAN RESEP MAKANAN DAN KUE BERBASIS ANDROID DENGAN MENGGUNAKAN FLUTTER - Dwi Saka Dharmawan; Ika Ratna Indra Astutik; Mochamad Alfan Rosid (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop an Android-based application to assist users, particularly young mothers, in cooking and learning various food and cake recipes. The application is designed to integrate traditional and modern recipes, providing an efficient platform for sharing recipes and interacting with the cooking community. Utilizing Flutter and Dart, this application offers rapid cross-platform development at a low cost, featuring a responsive and interactive user interface. The research was conducted at Rumah Makan Segar in Sidoarjo, employing data collection methods such as observation, interviews, and user surveys. The data was analyzed both quantitatively and qualitatively to evaluate user satisfaction and understand the perspectives of restaurant management and staff. The implementation results indicate that the application successfully creates an attractive and functional interface, supporting users in their cooking activities through features like culinary trend updates, a cooking community, and efficient recipe management. This application is expected to provide an effective solution for those looking to improve their cooking skills and explore various types of food recipes.